Application of the SAVI Model in Learning to Listen to Short Stories - ., Abdul Azis; Fatimah Yunus, Andi; Gunawan Saputra, Dedi (KnE Social Sciences, 2024)
The purpose of this research is to describe: (1) the components of short story listening skills, (2) the ability to listen after using the SAVI learning model; (3) the level of effectiveness of using the SAVI Model to teach students to listen to elements of short stories. It is a design that imagines a pseudo-experiment. The study population includes 20 students from class X. Cluster sampling was used, and pre- and posttest procedures were employed. Descriptive and inferential statistical approaches were used to analyze the data. As a result, (1) the ability to hear short story elements before the SAVI model is classified as low, (2) the ability to hear short story elements before the SAVI model is classified as high, and (2) the SAVI model showed an ability to hear elements of short stories before being classified as high. (3) The SAVI model applies effectively to learning story elements with tcount > ttable or 11.88 > 2.0414 at the 0.05 significance level. Based on the results of this study, the following suggestions are made: (1) Indonesian language and literature learning, especially literature listening, should be further improved by always providing students with short story listening training. (2) Teachers must use innovative teaching methods and learn to listen to elements of short stories. (3) To further improve their skills, students should actively practice listening to elements of short stories. Keywords: short stories, SAVI model, listening